The pressure–temperature phase diagram of tetramorphic pyrazinamide. Issue 28 (20th June 2022) - Li, Kangli; Gbabode, Gabin; Vergé-Depré, Marine; Robert, Benoit; Barrio, Maria; Itié, Jean-Paul; Tamarit, Josep-Lluis; Rietveld, Ivo B.
Abstract : All four pyrazinamide polymorphs possess a stable domain under ordinary pressure; α is the stable form at room temperature. Abstract : The phase behaviour of drug molecules is important for the control over the desired polymorph in drug formulations, whether it is to ensure better stability or better solubility. In the case of pyrazinamide, a drug against tuberculosis, stability studies have been complicated due to the very slow transition kinetics observed in DSC measurements. Using vapour pressure measurements, in which the reluctance of phase transformation is in fact an advantage, all solid–solid phase transformation temperatures have been determined. This method has been key to map the phase behaviour of pyrazinamide. The use of high-pressure measurements with synchrotron X-ray diffraction has allowed the construction of the pressure–temperature phase diagram of the four solid phases of pyrazinamide and the liquid phase. The α form was found to be the stable form at room temperature. One striking feature of pyrazinamide is that one polymorph, the δ form, has a very large thermal expansion and extreme compressibility not found in the other three forms. This gives rise to curved solid–solid transition equilibria in the pressure–temperature phase diagram, which is not commonly observed in the pressure range of 0 to 1 GPa. Using the phase diagram, polymorph β could be obtained in its stable temperature domain.